Solve for y cube root of 3y-2y=3

Math
3y-2y3=3
To remove the radical on the left side of the equation, cube both sides of the equation.
3y-2y33=33
Simplify each side of the equation.
Tap for more steps…
Multiply the exponents in ((3y-2y)13)3.
Tap for more steps…
Apply the power rule and multiply exponents, (am)n=amn.
(3y-2y)13⋅3=33
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
(3y-2y)13⋅3=33
Rewrite the expression.
(3y-2y)1=33
(3y-2y)1=33
(3y-2y)1=33
Subtract 2y from 3y.
y1=33
Simplify.
y=33
Raise 3 to the power of 3.
y=27
y=27
Solve for y cube root of 3y-2y=3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top